Constructing Identities: The ethno-national and nationalistic identities of white and Turkish students in two English secondary schools - Faas, Daniel (My University, 2008)
This article investigates how 15-year-old white and Turkish students in two Inner London comprehensive schools, one in a predominantly working-class area (Millroad School) and the other in a more middle-class environment (Darwin School), construct their identities. Drawing on mainly qualitative data from documentary sources, focus groups and semi-structured interviews, the work points to a range of factors affecting identity formation processes, such as macro-political approaches and school dynamics. The research found that at Millroad School, which celebrated diversity and where students? conflict was ethnic or racial, young people found safety in their national(istic) identities. In contrast, at Darwin School, which tried to integrate students on the basis of common British citizenship and where there was only low-level ethnic conflict, young people developed hybrid ethno-national identities. This article raises important questions about how to create community cohesion in conflictual environments so as to promote both diversity and solidarity.
PUBLISHED
Keywords: Hybridity; School dynamics; Social class; Community cohesion; Identities in Transformation; Inclusive Society; International Integration